Estimation of above-ground phytomass and carbon in tree resources outside the forest (TROF): A geo-spatial approach - Heyojoo, B. P.; Nandy, S. (Banko Janakari, 2015)
This study aims to estimate above-ground phytomass and carbon of TROF ecosystem in part of Bijnor district in Uttar Pradesh state of India using IRS P6 LISS-IV satellite image by geo-spatial approach coupled with field sampling. Chacko’s formula was referred to compute number of samples in each TROF types and the sample plot size in each stratum was adopted from Vegetation Carbon Project (VCP) under National Carbon Project (NCP). With the help of field data consisting mainly the height and girth information, volume of each individual tree per plot was obtained using site and tree species-specific standard volumetric equations. The phytomass was calculated by multiplying volume with Biomass Expansion Factor (BEF) then with regional specific gravity of the individual species and summed up in each plot to get total phytomass per plot. The total phytomass per plot was reported to be maximum 544.00 t/ha for linear TROF followed by 121.89 t/ha for block TROF. The carbon from phytomass was obtained by multiplying the total phytomass by a conversion factor that represents the average carbon content in phytomass. Spectral modeling for phytomass with different bands and indices were established and the best fit curve (R2 = 0.552) with red band was applied to generate phytomass and carbon distribution map of the study area. Banko Janakari, Vol. 24, No. 1, pp. 34-40